Study of the Effect of Inter-Electrode Distance on Thin Phytocyanine Zinc Thin Layer Resistance (ZnPc) with Exposure to Ozone - Nur Robi'ah A. M.; Anggriana Novitasari; Rachmat Triandi; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2015)
The effect of the distance between electrodes, in interdigitated pattern of Printed Circuit Board (PCB), on the resistance of zinc phthalocyanine (ZnPc) thin film have been done by measuring film resistance before and after ozone exposure. Interdigitated pattern of PCB was formed from copper layer by using FeCl3 10% as an etchant, with two various distance between electrodes i.e 0,3 mm and 0,7 mm. The thin film of ZnPc was deposited on the interdigitated electrode of PCB by using vacuum evaporation method, then, annealed at temperature 100ºC for 5h. The resistance of ZnPc thin film was measured before and after ozone exposure for 1h. The results show that the resistance of ZnPc thin film that deposited on PCB with the distance between electrodes 0,3 mm is 50% lower than in 0,7 mm, and, show the higher of the film conductivity. The higher of the film conductivity is caused by the larger of copper electrode surface that have conductive properties, on the PCB with smaller of the distance between electrodes.